Potato biodiversity: a linear discriminant analysis on the nutritional and physicochemical composition of fifty genotypes - Sampaio, Shirley L. (2018)
Fifty potato genotypes from twenty-four different countries of origin, four different flesh colours (yellow, purple, red and marble) and different cultivation types (Andean accessions, landraces, breeder lines and cultivated varieties) were studied in terms of their nutritional and physicochemical characteristics. In general, cultivated varieties and breeder lines showed the highest similarity (slight differences only in some particular fatty acids distributions: C10:0, C12:0 and C22:0) concerning the physicochemical parameters assayed in this work, independently of the geographical origin or tuber flesh colour of these genotypes. Nonetheless, some of the studied landraces and Andean accessions proved to be similar enough to be considered as genotypes with good potential for commercial cultivation. These results can contribute to the supply of new potato genotypes into sustainable farming systems, supporting the protection of potato biodiversity, particularly Andean accessions, landraces and coloured genotypes (red or purple flesh) which are not widely cultivated so far.